Prevalence of Gestational Diabetes Mellitus in Homagama Divisional Director of Health Service area - Ginige, S.; Wijewardhena, K.; Wijeyaratne, C.N. (My University)
Abstract Objective: To determine the prevalence of gestational diabetes mellitus (GDM) in the Homagama Divisional Director of Health Service (DDHS) area. Methodology: Eight hundred and fifty three pregnant women were subjected to a two-hour 75 g Oral Glucose Tolerance Test (OGTT) at period of amenorrhoea (POA) of 24 - 28 weeks.Results: The prevalence of GDM was 8.4 percent. the age standardized GDM prevalence was 10.3 percent [95 percent CI 7.3 - 13.4]. The prevalence of diabetes first detected during pregnancy was 1.2 percent and that of an impaired glucose tolerance (IGT) was 7.2 percent.Conclusions and Recommendations:Prevalence of GDM has increased among rural Sri Lankan pregnant women during the recent past. The majority (86 percent) of pregnant women with GDM belonged to the asymptomatic IGT category. This suggests the need for screening all pregnant women for GDM with a valid screening test during pregnancy instead of testing urine for reducing substances.
Keywords: gestational diabetes mellitus; prevalence; impaired glucose tolerance; pregnancy